2011
DOI: 10.1128/aem.00179-11
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Utilization and Selectivity of Pectin Fractions with Various Structures

Abstract: To evaluate the fermentation properties of oligosaccharides derived from pectins and their parent polysaccharides, a 5-ml-working-volume, pH-and temperature-controlled fermentor was tested. Six pectic oligosaccharides representing specific substructures found within pectins were prepared. These consisted of oligogalacturonides (average degrees of polymerization [DP] of 5 and 9), methylated oligogalacturonides (average DP of 5), oligorhamnogalacturonides (average DP of 10 as a disaccharide unit of galacturonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
94
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 41 publications
14
94
1
1
Order By: Relevance
“…more galactan and half the galacturonic acid content, findings which suggest that the galactan chains of the molecule have a more pronounced effect on the genus Lactobacillus, whereas the galacturonic acid chains may be favored by bacteria belonging to the genus Clostridium. It has previously been shown that in human feces, pectin fractions with neutral sugars were efficient in increasing the amount of Bifidobacterium organisms, whereas the amount of Clostridium bacteria was increased by polygalacturonic acid, as enumerated by fluorescent in situ hybridization (FISH) (61). In contrast, another study using a pectin fraction with high levels of galacturonic acid also showed by means of FISH little growth of clostridia and increased levels of Bifidobacterium (62).…”
Section: Figmentioning
confidence: 83%
“…more galactan and half the galacturonic acid content, findings which suggest that the galactan chains of the molecule have a more pronounced effect on the genus Lactobacillus, whereas the galacturonic acid chains may be favored by bacteria belonging to the genus Clostridium. It has previously been shown that in human feces, pectin fractions with neutral sugars were efficient in increasing the amount of Bifidobacterium organisms, whereas the amount of Clostridium bacteria was increased by polygalacturonic acid, as enumerated by fluorescent in situ hybridization (FISH) (61). In contrast, another study using a pectin fraction with high levels of galacturonic acid also showed by means of FISH little growth of clostridia and increased levels of Bifidobacterium (62).…”
Section: Figmentioning
confidence: 83%
“…Prebiotics, oligo pectins have been shown to be better prebiotics for specific probiotic bacteria like Bifidobacteria and Lactobacilli. The selectivity of oligosaccharide depend on the chain length and presence of specific functional groups, the oligo pectins with short chain being preferred substrate for probiotics [80,81].…”
Section: Potential Applications Of Modified Pectinmentioning
confidence: 99%
“…Although, there was no significant difference in the number of faecal lactobacilli count between the MCP-treated mice and control (p > 0.05), the reduced faecal lactobacilli presented by MCP-treated mice corroborates the observation made by Doyle (2007), Biagi et al (2010) and Zhong et al (2014) that pectin stimulates bacteria other than lactic acid bacteria. Conversely, some studies showed that citrus pectin encourages the proliferation of lactobacillus species which is dependent on the composition and prebiotic index of the pectic fraction-arabinan and galactan (Dnumpai et al, 2011), degree of methylation and selective fermentation of pectin (Dlano-Martin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%